Recycling and reuse performance of cobalt catalyst for coal hydrogasification. (1st March 2023) - Feng, Jun; Yan, Shuai; Zhang, Rong; Gu, Sumin; Qu, Xuan; Bi, Jicheng
Highlights: Acid leaching was used to recover Co catalyst from coal hydrogasification residue. HNO3 -leached efficiency of cobalt exceeded 99.7% in each closed-loop cycle. Enrichment behaviors of 17 impurities in the recovered solution were revealed. Effects of Fe, Al, K, Na, Mg, P, and S impurities on Co–Ca activity were assessed. Using selective precipitation to remove impurities and regenerate Co–Ca activity. Abstract: Hydrogasification (C + H2 → CH4 ) is a crucial reaction for obtaining CH4 from coal or biomass. However, the reaction is sluggish in the absence of a suitable catalyst. Cobalt is more catalytically active than iron, nickel, and alkali metals, but is expensive. To improve the process economy, catalyst recycling was investigated with a focus on cobalt and calcium (Co–Ca) catalyzed coal hydrogasification. The results revealed that Co existed as metallic state in the gasified residue, and it was strongly associated with Ca compounds. Co–Ca as nitrate and acetate exhibited significantly higher activity than that of chloride and sulfate. Nitrate acid (HNO3 ) can effectively leach Co and Ca from the residue, as the leaching efficiencies of Co and Ca exceeded 99.7 % and 98.0 %, respectively. Additionally, seventeen mineral impurity elements were extracted from the residue. With repeated recycling, the majority of impurities accumulated in the recovered catalyst and exhibited distinct effects on its activity. Al impurity demonstrated its ability to significantly lower the Co–Ca activity, whereas Fe, K, Na, Mg, P, and S could not. Because impurities inhibited Co reducibility, the catalytic performance of recovered Co–Ca decreased with each recycling. Inspired by the results, the proposed HNO3 leaching procedure was optimized using two-step precipitations for impurities removal, and a high activity of recovered catalyst was achieved. This study provides some insights into the recovery, deactivation, and regeneration of cobalt catalyst employed for coal or biomass hydrogasification.